Forgiveness and Reconciliation between Poles and Germans as a Gift and Task. 50 Years after the Exchange of Letters of Polish and German Bishops - Henryk J. Muszyński (Paedagogia Christiana, 2016)
The article shows the importance of “The Message of the Polish bishops to their German brothers in Christ's pastoral office” (November, 18 1965) in the history of Polish-German reconciliation. This Message contained the famed phrase “we forgive and ask for forgiveness” directed, at the conclusion of Vatican II, to the German bishops by representatives of the people, who were the victim of World War II. This phrase, over the past fifty years,  had become a source of some confusions first, but, eventually,  it brought to the peoples and to the believers of Churches living in Poland and Germany blessed fruits, which were the foundations for further Polish-German relations. It is therefore not strange that this Message of Polish bishops is now considered by many historians as the most important document of the postwar period. The article, in  its four parts, reveals religious themes, efforts and activities of Polish bishops which aimed at deepening the sense of forgiveness and reconciliation in the midst of shaping the attitudes of the faithful living in the Roman Catholic Church in Poland. The decisive event in this respect - apart from Vatican II – was the celebration of 1000th anniversary of the Baptism of Poland, celebrated at Jasna Gora in Czestochowa on 3th May 1966,  under the leadership of the Primate of Poland Stefan Cardinal Wyszynski. Further sections of the article show a long and laborious process of ripening of the forgiveness in the dimension of community and society. This process is illustrated by other - this time common - documents Polish and German bishops issued on the occasion of the 30th (1995) and 40th anniversary (2005) of first “Message”, and recently culminated with a solemn celebration of Polish and German bishops in Czestochowa, on November, 22 2015 and completed by the first joint Message of Polish and German Presidents. The process of rapprochement, dialogue and reconciliation, which began with a collective act of forgiveness has led to far-reaching political changes, lasting peace in Poland and much of Europe. Presented in the article's Messages and their impact on Polish and German societies clearly show that there is no peace without justice, but – as well –  there is no justice without forgiveness.